The effect of personalized feedback on listening and reading skills in the learning of EFL. Issue 3 (4th March 2022) - Pérez-Segura, José Jaime; Sánchez Ruiz, Raquel; González-Calero, José Antonio; Cózar-Gutiérrez, Ramón
Abstract: The present study firstly assesses how students can develop and improve the skills of listening and reading through personalized feedback. Secondly, it evaluates the motivational effects of the use of Audience Response Systems (ARS) in English lessons in comparison with the lessons where these electronic devices are not used. In three sessions, 68 sixth-grade students did exercises of reading and listening based on their errors, while other 68 students–the control group–completed generic activities working on those skills. Clickers, ARS devices, were used in both groups as a tool for gathering students' answers, and the Reduced Instructional Materials Motivation Survey (RIMMS) was employed to evaluate their influence on students' motivation in the English subject. The results show that both groups were more motivated with the use of clickers and that the group with personalized feedback improved their receptive skills more than the control one, especially in the general information variables.